Early decrease of serum biomarkers of type II collagen degradation (Coll2‐1) and joint inflammation (Coll2‐1 NO2) by hyaluronic acid intra‐articular injections in patients with knee osteoarthritis: A research study part of the Biovisco study. Issue 6 (19th February 2013) - Henrotin, Y.; Chevalier, X.; Deberg, M.; Balblanc, J.C.; Richette, P.; Mulleman, D.; Maillet, B.; Rannou, F.; Piroth, C.; Mathieu, P.; Conrozier, T.
Abstract To measure the evolution of the serum levels of specific Osteoarthritis (OA) biomarker, Coll2‐1 and Coll2‐1 NO2 in knee osteoarthritic patients after viscosupplementation (VS). Fifty‐one patients with unilateral symptomatic knee were recruited for this prospective open label study. They received three intra‐articular injections of 2 ml of hyaluronic acid (Hylan GF‐20) and were followed for 3 months. Walking pain was evaluated and serum samples were taken at each visit. Coll2‐1 and Coll2‐1 NO2 were measured in the serum using specific immunoassays. Variations over time of each parameter and predictive factor of response were studied. Forty‐five patients were analyzed. The serum concentrations of Coll2‐1 and Coll2‐1 NO2 were significantly higher in KL III/IV patients compared to KL I/II patients at baseline and decreased systematically over time after VS. Its effect was ever more pronounced in patients with KL III/IV. The serum concentration of Coll2‐1 was significantly lower at baseline in responders than in non‐responders. This study suggests a rapid slowdown of type II collagen degradation and joint inflammation after VS with Hylan G‐20 and gives additional information for the validation of accurate biomarkers for OA. The serum level of Coll2‐1 appeared to be a predictive factor for response to treatment. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 901–907, 2013